Semiotic Analysis of Cartoon Content on the Instagram Account Feed of the President of the Republic of Indonesia @Jokowi - Rahman, Radif; Septariza, Dodi; Nazurah Setiawan, Filzah (Journal of Law, Politic and Humanities, 2024)
In the era of growing technological developments, the delivery of messages is not only done directly but can also be delivered indirectly through social media. Instagram social media is one of the places to communicate. This study aims to understand the signs and visual meaning of the cartoon content on the @jokowidodo account feed on January 1, 2024 which contains Happy New Year greetings using Ferdinand De Saussure's semiotic theory. The method used is a descriptive qualitative method with a constructivist / interpretative paradigm. The results of the study found that there are 25 contents in one "Happy Birthday 2024" upload on the @jokowi account where each content has its own meaning such as the content "Kesmas Services" has the meaning that Joko Widodo wants to convey the priority of health services for people in all parts of Indonesia by making the 2024 health budget which has been planned at Rp. 186.4 trillion or 5.6% of the total APBN. This figure is 8.1% or Rp 13.9 trillion larger than in 2023. Political messages are also tucked away in the content, conveying the President's message of closeness to one of the 2024 Election Presidential candidates. So that the upload of the greeting "Happy Birthday 2024" is not only limited to greetings and hopes but also displays various kinds of Indonesian achievements until 2024 that have been carried out by President Joko Widodo.